The Development of Mosque Architecture in Islamic History: A Study of the Acculturation of Islam and Local Culture in the Archipelago - Hajar, Imam Ibnu; Hawari, Muhammadudy Hisyam; Rabbani, Muhammad Syiham (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Mosques are central institutions in Islamic civilization, serving not only as places of worship but also as centers of social, educational, and political activity. With the expansion of Islam into various regions, mosque architecture underwent significant transformations in response to social dynamics and cultural interactions. This study aims to analyze the process of acculturation and transformation of mosque architecture throughout Islamic history and to examine the distinctive characteristics of mosque architecture in Indonesia from the perspective of continuity and change.This research uses a qualitative approach with historical methods, encompassing heuristics, source criticism, interpretation, and historiography. A cultural approach is used to understand the interaction between Islamic values ​​and local culture, while a theoretical framework of continuity and change is used to analyze the relationship between elements of continuity and change in the development of mosque architecture.The results show that mosque architecture throughout Islamic history is dynamic and contextual. It does not possess a single, universal form but rather develops according to local social, political, and cultural conditions. In the Indonesian context, mosque architecture exhibits distinctive characteristics through its overlapping roof shape, rectangular floor plan, use of local materials, and the presence of verandas and walled courtyards, reflecting the continuity of pre-Islamic architectural traditions. Meanwhile, elements such as the mihrab (prayer niche), the orientation of the Qibla (prayer direction), and the function of congregational prayer demonstrate the transformational aspects brought about by Islamic teachings.The main findings of this study confirm that mosque architecture in Indonesia is not simply the result of adopting foreign traditions, but rather the result of active cultural negotiations between locality and the universality of Islam. Thus, mosques in Indonesia can be understood as representations of Islamic civilization that are adaptive, contextual, and uniquely Indonesian.